A sidecar named desire : great writers and the booze that stirred them - Beauchamp, Monte (Dey Street, an imprint of William Morrow, 2018)
"A rollicking illustrated history of alcohol and its literary imbibers, from Jane Austen's beer brewing to James Joyce's passion for Guinness to E.B. White's cure for writers' block--a dry martini--by celebrated New Yorker cartoonist Greg Clarke and award-winning comics anthologist Monte Beauchamp" --